Effectiveness of green tea, bay leaf, and lime peel extracts as toothpastes active agents for extrinsic stain removal on teeth, artificial teeth, and denture base - Annisa, Mutiara; Kanina, Puteri Aulia Rizqi; Hamid, Nur Liyana Binti; Nuryanti, Archadian (Universitas Padjadjaran, 2022)
Introduction: Tea consumption causes extrinsic stain formation on teeth and denture surfaces, affecting personal appearance. Herbal plants extract such as green tea, bay leaf, and lime peel are potentially active agents for extrinsic stain removal. This study aimed to analyse the effectiveness of green tea, bay leaf, and lime peel extracts as toothpaste active agents for extrinsic stain removal on teeth, artificial teeth, and denture base. Methods: Twenty-five post-extracted human permanent central incisors, 25 artificial teeth, and 25 heat polymerised acrylic resin denture base (20x20x10mm) were divided into three treatment groups and two control groups. Pictures of all specimens were taken before and after stain induction and after brushing. All specimens were immersed in a tea solution made from 2 grams of tea and 100ml of 100°C boiled water to induce extrinsic stain. The immersion process was repeated every 24 hours for seven days. All specimens were then brushed using an automatic toothbrushing machine for 70 seconds on each surface, 200 grams loads, and five speeds/second. Toothpaste used for brushing were three different active agent toothpaste (treatment groups), no active agent toothpaste, and commercial whitening (control groups). Colour index analysis of the specimen pictures computerised by CIELAB method. The data were analysed by one-way ANOVA (α=0.05). Results: Green tea, bay leaf, and lime peel extract toothpaste and positive control had higher L-values of extrinsic stain removal than essential toothpaste on all specimens. There was a significant difference between green tea, bay leaf, and lime peel extract toothpaste and negative control toothpaste (p<0.05), while no significant difference was found when compared to the positive control toothpaste (p>0.05). Conclusion: Green tea, bay leaf, and lime peel extract toothpaste are effective as extrinsic stain removal on teeth and acrylic resin denture base because of abrasive materials that work together with the active agents such as epigallocatechin-3-gallate (EGCG) in green tea, eugenol in bay leaf, and naringin in lime peel.